The Reality of Empowering Women Working in the Service of Pilgrims within the Hajj and Umrah System - AlOsaimi, Fatimah Ayidh; Alotybi, Saad Azeez (The Arab Journal of Administration, 2025)
The Kingdom of Saudi Arabia has made great strides in terms of empowering women and has been supported to assume leadership positions in various fields. However, the woman working in the Hajj and Umrah system remained an unknown soldier despite her constant presence and work in the service of the guests of Allah, especially women and children among them, and official statistics in the Kingdom indicate He pointed out that the number of Rahman’s guests annually is estimated at 40% of the total number of pilgrims, and that the workforce of women during the past five years did not exceed 7% of the total number of workforce serving pilgrims.This study aimed to assess the current reality of empowering women working in the service of the pilgrims through the opportunities and challenges they face, from the point of view of a sample of (130) female employees and volunteers. Guests of Rahman, and the questionnaire was relied on as a tool for collecting data related to the study, and the results showed that the majority of the sample members agreed with a percentage of 78.2% that there are opportunities available to support the empowerment of women working in the Hajj and Umrah system to a high degree, and that the majority of the sample members agree with a percentage of 64.5% that there are challenges that hinder It limits the empowerment of working women to a medium degree, and the study recommended raising the percentage of women’s employment in the Hajj and Umrah system, as the current percentage does not look forward to the goals of Vision (2030) in empowering Saudi women, and adopting the concept of empowerment for female workers in the service of pilgrims more effectively by deciding their role Increasing the percentage of their participation in decision-making centers, diagnosing the most important personal obstacles and obstacles within the work environment that prevent female workers from advancing and empowering them, and working on studying them to find appropriate solutions to treat it.